THE INTERNATIONAL EXPERIENCE OF THE STRATEGY AND MARKETING POLICY FORMATION OF HOTEL BUSINESS ENTERPRISES - SAMOILYK, IULIIA; STEBLIUK, NATALIIA; KUCHER, MARHARYTA; SAIHAK, YELYZAVETA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The hotel business is an integral part of the economies of countries and their regions. Its condition is an indicator of overall development, as well as shaping the rating and image of countries in the international environment. This type of activity is quite risky, which is associated with significant investment in construction, reconstruction, the need for constant renewal, the introduction of new equipment and maintenance technologies; significant dependence on the human factor - both on the part of customers and staff; integration into the global space and the need to take into account global trends, etc. The riskiness of the industry is clearly demonstrated by the period of the pandemic caused by COVID-19. Most hotels have failed to respond effectively to new challenges related to restrictions on international and domestic travel, the need to comply with increased sanitation requirements and work in conditions of uncertainty. A number of hotels went bankrupt or suffered significant losses. If by 2019 in most countries of the world it was possible to trace the growth of the main indicators of hotel business development both from the growing demand and in the direction of new technologies in the hospitality industry, then in the current crisis positive trends have stopped. The current conditions in which the world, and in particular the hotel business, found themselves, require the formation of new strategic development plans, as well as marketing policies, which will reflect globalization challenges and current progressive trends. The purpose of the article is to identify the features of the development strategy and marketing policy formation of the hotel business in the global context based on the identification of basic imperatives and features for each country or region. Approaches to the strategy and marketing policy formation of hotel business enterprises have been further developed. The scheme reflecting the basic imperatives of this process has been constructed. It has been substantiated that the marketing strategy, on the basis of which the marketing policy and complex is formed, is a component of the general basic strategy of enterprise development and is interconnected with such functional strategies as strategy of hotel services, personnel, financial and investment, logistics. It has been proved that the main determinants of the development strategy and marketing policy of the hotel business are the development of international and national hotel chains, authentic independent hotel companies, global and national trends in hospitality and tourism, consumer demands and preferences, limitations caused by the pandemic. In order to compare the potential of countries and identify their features for the development of hotel and tourism business, the Travel and Tourism Competitiveness Index (TTCI) has been considered.